Isu Gender dalam Reformasi Hukum Perkawinan di Negara-Negara Islam - Tengku Rizki Rahman; Heriandi Heriandi; Ibnu Radwan Siddik Turnip; Rahmad Efendi (Lembaga Yasin AlSys, 2026)
Although marriage law reform in Muslim-majority countries has received sustained academic attention, studies that systematically classify reform trajectories based on the interaction between the legitimacy of sharīʿa, state authority, and gender justice remain relatively limited. This study aimed to analyze how Muslim states negotiate women’s rights in Islamic family law through different models of legal reform. Employing a qualitative, historical–comparative approach in legal studies, it examines statutory texts, judicial practice, and law reform policies in selected Muslim-majority jurisdictions. Data were obtained from primary legislation, court decisions, and authoritative secondary literature and were analyzed using comparative legal reasoning and thematic analysis. The findings identify three main reform models. The conservative–traditional model, evident in Saudi Arabia, Pakistan, and several Gulf states, maintains classical fiqh with minimal state intervention, thereby perpetuating hierarchical gender relations. The moderate–codificatory model, implemented in Egypt, Morocco, Jordan, and Indonesia, selectively modifies fiqh through state codification and judicial oversight, enabling incremental gender reform. The secular–progressive model, as exemplified by Turkey and Tunisia, reconstructs family law by discarding sharīʿa as the basis of state law, abolishing male guardianship, prohibiting polygamy, and institutionalizing more gender-equal forms of divorce. This study concludes that Islamic marriage law reform does not move linearly toward secularization but rather produces a spectrum of normative arrangements shaped by configurations of political authority, interpretive choices in law, and evolving gender discourses. These findings contribute to the development of comparative Islamic law theory and offer policy-relevant implications for the design and implementation of future family law reforms.